Serotype 3 Experimental Human Pneumococcal Challenge (EHPC) study protocol: dose ranging and reproducibility in a healthy volunteer population (challenge 3) - Maia Lesosky; Konstantinos Liatsikos; Stephen B Gordon; Kelly Davies; Phoebe Hazenberg; Angela Hyder-Wright; Ryan E Robinson; Britta Urban; Elena Mitsi; Carla Solorzano; Daniela M Ferreira; Madlen Farrar; et al. (BMJ Open, 2024)
Introduction Since the introduction of pneumococcal conjugate vaccines, pneumococcal disease rates have declined for many vaccine-type serotypes. However, serotype 3 (SPN3) continues to cause significant disease and is identified in colonisation epidemiological studies as one of the top circulating serotypes in adults in the UK. Consequently, new vaccines that provide greater protection against SPN3 colonisation/carriage are urgently needed. The Experimental Human Pneumococcal Challenge (EHPC) model is a unique method of determining pneumococcal colonisation rates, understanding acquired immunity, and testing vaccines in a cost-effective manner. To enhance the development of effective pneumococcal vaccines against SPN3, we aim to develop a new relevant and safe SPN3 EHPC model with high attack rates which could be used to test vaccines using small sample size.Methods and analysis This is a human challenge study to establish a new SPN3 EHPC model, consisting of two parts. In the dose-ranging/safety study, cohorts of 10 healthy participants will be challenged with escalating doses of SPN3. If first challenge does not lead into colonisation, participants will receive a second challenge 2 weeks after. Experimental nasopharyngeal (NP) colonisation will be determined using nasal wash sampling. Using the dose that results in ≥50% of participants being colonised, with a high safety profile, we will complete the cohort with another 33 participants to check for reproducibility of the colonisation rate. The primary outcome of this study is to determine the optimal SPN3 dose and inoculation regime to establish the highest rates of NP colonisation in healthy adults. Secondary outcomes include determining density and duration of experimental SPN3 NP colonisation and characterising mucosal and systemic immune responses to SPN3 challenge.Ethics and dissemination This study is approved by the NHS Research and Ethics Committee (reference 22/NW/0051). Findings will be published in peer-reviewed journals and reports will be made available to participants.